Comparison of the effect of aerosolized fibrin sealant and biodegradable synthetic polyurethane foam on hemostasis and wound healing after endoscopic sinus surgery: a prospective randomized study. Issue 11 (31st August 2017) - Jung, Moon Sik; Choi, Chang Hwan; Yu, Myeong Sang
Abstract : Background: Use of absorbable packing materials after functional endoscopic sinus surgery (FESS) is associated with increased patient comfort and a lack of need for packing removal. Different materials may induce different patterns of mucosal healing and hemostasis. This study investigated the effect of fibrin sealant (FS; Tisseel) or biodegradable synthetic polyurethane foam (Nasopore ® ) packing on hemostasis and wound healing after FESS. Methods: This prospective randomized controlled trial included 35 consecutive patients who underwent bilateral FESS for chronic rhinosinusitis. The patients were randomized to receive FS through aerosol spraying on 1 side and Nasopore packing on the opposite side. They were followed at 1, 2, 4, 8, and 12 weeks after surgery. Endoscopically visible packing material, crusting, adhesion, bleeding, granulation tissue formation, frontal sinus patency, and adverse effects were assessed. Subjective symptoms related to nasal packing were evaluated by using questionnaires quantified with a visual analogue scale. Results: No significant differences were found between the FS‐treated side and the Nasopore‐packed side with respect to postoperative bleeding, adhesion, or frontal sinus patency. However, crusting and granulation were significantly lower in FS‐treated nostrils ( p < 0.01). The patients' satisfaction and willingness to reuse the material were not significantly different between FS and Nasopore. There were no allergic reactions to either material. Conclusion: FS and Nasopore were equally successful in achieving hemostasis and patient satisfaction after FESS. However, our results suggest that differential mucosal healing patterns may be induced by alternative absorbable hemostatic materials. FS‐treated sides showed more optimal healing patterns than Nasopore‐packed sides.